2020
DOI: 10.2478/rtuect-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Factors Affecting Onshore Wind Power Deployment in India

Abstract: AbstractThe Present study focuses on the impact of various factors on the growth of wind power generation in seven most wind energy prone states of India, that contain 97 % of India’s total wind power potential. The impact of state-wise policy parameters Feed-in Tariff (FIT) rate, Renewable Purchase Obligations (RPO) and Power Purchase Agreement (PPA) are evaluated in terms of aggregate policy indices that indicate the likelihood of wind power deployment in that state, through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Wind power is affected by wind [9]. e wind in nature is related to meteorological factors such as temperature, air pressure, and humidity.…”
Section: Data Collection and Transmissionmentioning
confidence: 99%
“…Wind power is affected by wind [9]. e wind in nature is related to meteorological factors such as temperature, air pressure, and humidity.…”
Section: Data Collection and Transmissionmentioning
confidence: 99%
“…Pr government policies on the economics of the power projects which leads to lower system costs 31 has not been evaluated so far for the hybrid energy system. In order to bridge the research gap, the objective of the present study is to apply instantaneous multidimensional 6E analysis (energy, exergy, economic, environmental, advance exergy and exergoeconomic (extended exergy)) on a 5.6 MW HWSES having equal wind and solar installation capacity (2.8 MW each for wind turbine and solar PV) (Figure 1).…”
Section: Extended Exergiesmentioning
confidence: 99%
“…NPV indicates the net value of the energy project at the end of the project lifetime, whereas the LCOE is the cost of energy generation per unit of power generation. 45 Both NPV and LCOE are based on the net cash flow approach; therefore, any one of these parameters is sufficient for the representation of the system economics. The expression of LCOE remains the same for any kind of power generation system as given in Table 3.…”
Section: Economic Assessment (5e)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it concluded that 1/4 of the wind power plants installed by then could not withstand power outages, subsequently creating an excellent opportunity for the wind repowering market. Recently, in 2020, Das et al analyzed the main factors that were influencing the onshore wind energy deployment in India, being the presence of repowering policy one of them [95]. However, in that country, only four states have such type of politics.…”
Section: Single-category Analysismentioning
confidence: 99%